Irish banks and amalgamation - Kelly, Richard J. (Statistical and Social Inquiry Society of Ireland, 1919)
British and with them, of course, Irish Banks are now face to face with an unprecedented and, for them, very anxious condition of things, and British and Irish Banking may in a sense be thought to be nearing a crisis. Their present, and so far successful, methods of doing business may be said to be on their trial. To provide for the changed financial situation many expedients will have to be resorted to, many new plans adopted, a different system set up, perhaps.
The recent British bank amalgamations and Ireland
Read March 21st, 1919
Keywords: Bank mergers; Ulster Bank; 314.15